Clinical supervision in a quality assurance/quality improvement system: Multisystemic Therapy† as an example. (14th October 2016) - Schoenwald, Sonja K.
Abstract: This article describes the clinical supervision of Multisystemic Therapy (MST), which takes place in the context of a quality assurance and quality improvement system that is used to support the transport and implementation of MST nationally and internationally. Information is provided about the assumptions, objectives, structure, process, and content of MST supervision; training and support provided to supervisors; methods used to measure adherence to the supervision model; and, findings supporting linkages between supervision, therapist adherence, and youth outcomes. MST supervision is considered in the context of recent efforts to identify empirically supported approaches to supervision and of recent developments in implementation research.